Phycochemical and Biological Activities From Different Extracts of Padina antillarum (Kützing) Piccone - Samar, Juveria; Butt, Ghazala Yasmeen; Shah, Anis Ali; Shah, Adnan Noor; Ali, Sajad; Jan, Basit Latief; Abdelsalam, Nader R.; Hussaan, Muhammad (Frontiers in Plant Science, 2022)
Seaweeds are non-vascular, photosynthetic that inhabit the coastal regions commonly within rocky intertidal or submerged reef-like habitats and have been one of the richest and most promising sources of bioactive primary and secondary metabolites with antimicrobial properties. They selectively absorb elements like Na, K, Ca, Mg, I, and Br from the seawater and accumulate them in their thalli. Padina antillarum (Kützing) Piccone is the member of Phaeophycota, have remarkable phycochemistry as well as bioactivity. The phycochemical tests of the different extracts showed the presence of alkaloids, terpenoids, saponins, tannins, steroids and phenols. The relative percentage of Oxirane, tetradecyl (C16H32O) and Cyclononasiloxane (C18H54O9Si9) is higher while Tetrasiloxane (C16H50O7Si8) in GC-MS analysis. FRAP, %inhibition, total antioxidant value of Padina antillarum was higher in methanolic extract. Hexane, Chloroform extract showed no zone of inhibition against B. subtilis, E.coli, K. pneumonia, S. aureus and S. epidermidis. The methanolic extract of Padina antillarum exhibit maximum zone of inhibition against S. epidermidis (18.66±0.09). Antifungal activity of the Padina antillarum Hexane extract exhibited no zone of inhibition against Aspergillus niger and Penicillium notatum while the chloroform extract yields maximum zone. Diabetes mellitus is one of the most familiar chronic diseases associated with carbohydrates metabolism. It is also an indication of co-morbidities such as obesity, hypertension and hyperlipidemia which are metabolic complications of both clinical and experimental diabetes. The treatment of Padina antillarum extract to mices reduced the body weight loss, low level of triglycerides, elevated HDL cholesterol level as compare to diabetic mices.